The Impact of Semantics Awareness on English Learning Anxiety: A Study of Perceptions of 6th Semester Students at University Muhammadiyah of Tangerang - Wulandari, Siti; Alkhobir, Zami Aqil; Putra, Aidil Syah (Indonesian Journal Publisher, 2024)
This study investigates the impact of semantic awareness on English learning anxiety among sixth-semester students at Universitas Muhammadiyah Tangerang, utilizing a mixed-methods approach. The research surveyed 10 students (5 from class A1 and 5 from class A2). Both quantitative and qualitative analyses were conducted to explore the relationship between semantic awareness and learning anxiety. Findings indicate that students with higher semantic awareness reported better comprehension and use of English in academic and social contexts, suggesting a significant connection between these factors. The study highlights practical applications for language education, emphasizing the importance of enhancing semantic awareness to reduce anxiety and improve language learning outcomes. These results provide valuable insights for educators in designing effective language learning strategies, ultimately aiming to foster a more supportive and less anxiety-inducing learning environment for students.